Public speaking anxiety and its relationship with attitude and motivation among Jordanian EFL learners - Alsaleem, Alaa Abdullah Mesleh (2023)
This study aimed at identifying the attitudes of Jordanian EFL learners toward English public speaking skills. Secondly, it is intended to identify the motivational level of Jordanian EFL learners and to determine if they have integrative or instrumental motivation toward English public speaking skills. Besides, it aimed to investigate how attitude and motivation affect English public speaking anxiety. Lastly, it aimed to explore how Jordanian EFL learners perceive their English public speaking anxiety. The study employed a mixed-methods research design. Based on non-probability purposive sampling, 191 Jordanian PhD EFL students responded to the questionnaire. Besides, interviews were conducted with six Jordanian PhD EFL students. The findings indicated that the attitude of Jordanian EFL learners towards English public speaking was low. More precisely, the result indicated that most Jordanian EFL learners (PhD students) have a negative attitude toward speaking English in public. Moreover, Jordanian PhD students had a low level of motivation. Besides, it was found that even though the motivation level of students towards English public speaking skills was low, they can be motivated instrumentally. Additionally, attitude and motivation were significantly correlated with English public speaking anxiety, suggesting that English public speaking anxiety among Jordanian EFL learners was negatively affected by their attitude and their level of motivation. Lastly, qualitative findings are consistent with the quantitative findings, supporting the fact that students had a negative attitude and low motivation toward speaking in English in public. The results have many outcomes for EFL teachers and policymakers, all of which may benefit EFL students by increasing their motivation and enhancing their attitude toward speaking English in public, hence reducing their level of anxiety.